Spontaneous coronary artery dissection in a young woman resolved with conservative strategy. A case report - Di Marco, Massimo (J Cardiol Cases, 2016)
Spontaneous coronary artery dissection (SCAD) is a rare disease associated with high mortality rate, whose etiology and pathogenesis has been poorly understood to date. The management of these patients is still controversial. A young, otherwise healthy woman, without known underlying conditions leading to SCAD, was admitted to our Intensive Cardiology Care Unit; she had history of intense psychological stress. She was managed with a conservative approach based on watchful waiting and medical therapy. She had an uneventful course. This is a rare case of SCAD where stable hemodynamics allowed us to adopt a conservative approach. <Learning objective: Spontaneous coronary artery dissection (SCAD) is a rare disease associated with high mortality rate, whose etiology and pathogenesis has been poorly understood to date. The management of spontaneous coronary artery dissection (SCAD) is still debated due to the rarity of cases; to treat or not to treat invasively? In our case, the hemodynamic stability of the patient suggested to wait and watch with serial angiographies and medical therapy. The uneventful course ruled in favor of our choice. Thus, the take home message is that not all cases of SCAD deserve to be treated with invasive procedures.>